2008
DOI: 10.1111/j.1540-5834.2008.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

I. Theoretical, Empirical, and Practical Rationale

Abstract: A fundamental quest of the developmental social and behavioral sciences is to specify the necessary and sufficient early experiences that lead to typical human development in childhood and adulthood. Because the opportunity to experimentally manipulate early human experiences is very limited, one approach is to observe the development and long-term outcomes of children who are tragically reared in atypically deficient early environments.Unfortunately, these studies usually are limited by a variety of confounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 135 publications
1
28
0
8
Order By: Relevance
“…Although Time in BH (months) was not different for children who transitioned to different types of families in a previous study (McCall et al, 2014), it was related to the extent of BH intervention effects on children’s development at departure (St. Petersburg-USA Orphanage Research Team, 2008) and it is generally related to longer-term outcomes for post-institutionalized children (Julian, 2013).…”
Section: Data Analysis Strategymentioning
confidence: 73%
See 1 more Smart Citation
“…Although Time in BH (months) was not different for children who transitioned to different types of families in a previous study (McCall et al, 2014), it was related to the extent of BH intervention effects on children’s development at departure (St. Petersburg-USA Orphanage Research Team, 2008) and it is generally related to longer-term outcomes for post-institutionalized children (Julian, 2013).…”
Section: Data Analysis Strategymentioning
confidence: 73%
“…Petersburg-USA Orphanage Research Team, 2005, 2008), which was designed to promote caregiver-child relationships and provide children with more stimulation. Three institutions for children birth to four years called Baby Homes (BHs) received one of three conditions.…”
Section: The St Petersburg Interventionmentioning
confidence: 99%
“…Residential child care institutions, known as orphanages in Rwanda, rarely meet the average acceptable environmental conditions for children’s normal development (1). They often lack stable caregiving as well as open opportunities for exploration and mastery of the world (2, 3).…”
Section: Introductionmentioning
confidence: 99%
“…Ten percent of children are born preterm worldwide (World Health Organization, 2015), and the most recent data in the Russian Federation (RF) shows 4.3% are preterm (Skripnichenko, Baranov, & Tokovaya, 2014). Some studies reported that there is a substantial number of preterm children in institutions for children left without parental care (Chernego, 2015; The St. Petersburg-USA Orphanage Research Team, 2008; Vorria et al, 2003). In the RF in 2014, there were nearly 28 million children, 50,227 of them lived in 1076 institutions for children 0–18 years old, and 11,530 lived in Baby Homes (BH) for children 0–4 years old (Ministry of Labour and Social Protection of the Russian Federation, 2014).…”
mentioning
confidence: 99%
“…Generally, children exposed to the psychosocial deprivation of institutional care display deficiencies in development (van IJzendoorn et al, 2011). Interventions in institutions have produced developmental improvements in physical and developmental domains for children (Groark et al, 2013; The St. Petersburg-USA Orphanage Research Team, 2008). Despite the presence of preterm children in orphanages, this group has never been studied specifically.…”
mentioning
confidence: 99%